Are Emotions Evaluative Modes?. (September 2015) - Dokic, Jérôme; Lemaire, Stéphane
Abstract: Following Meinong, many philosophers have been attracted by the view that emotions have intrinsically evaluative correctness conditions. On one version of this view, emotions have evaluative contents (the Perception View). On another version, emotions are evaluative attitudes; they are evaluative at the level of intentional mode rather than content (the Attitudinal View). We raise objections against the latter version, showing that the only two ways of implementing it are hopeless. Either emotions are manifestly evaluative or they are not. In the former case, the Attitudinal View threatens to collapse into the Perception View or any other view according to which emotions are evaluative at the level of content. In the latter case, the Attitudinal View does not stand up to an obvious alternative, namely that emotions can only be assessed with respect to extrinsic (moral, prudential, aesthetical, etc.) norms or conditions of correctness.